Hubungan Tingkat Pengetahuan Perawat dengan Tindakan Keperawatan pada Pasien Pasca Operasi dengan General Aenesthesia di Ruang Pemulihan IBS RSD dr. Soebandi Jember - Riezky Dwi Eriawan; . Wantiyah; Anisah Ardiana (Pustaka Kesehatan, 2013)
Knowledge comes from education, teaching, training and experience. The higher the education of a person, the knowledge level. Will be the knowledge is influential factor in performing a nursing actions, the better the knowledge of nurses the better the action taken by nurses in managing postoperative patients. The design of this research was study correlation with observational analytic study used cross sectional method. The sampling technique used was total sampling. Research sample in this study were 20 nurses in the recovery room, the the data analysis used chi-square statistical test with 95% Cl (α : 0.05) in get (p value : 0.005), these result indicate that p value is lower than the significant level (p <0.05), so there is a correlation between nurse’s knowledge level and nursing actions of postoperative patients with general anesthesia in the recovery room IBS RSD dr. Soebandi Jember. The result showed that 18 respondens (90%) nurses have a good knowledge and 18 respondens (90%) nurses have a good nursing action.Hopefully the leader of the room give support to the nurses in the recovery room so that nurses can improve and increase their knowledge and skills of nursing’ in managing postoperative patients. Keywords: Knowledge level, Nursing Action of Postoperative Patiens, General Anesthesia